Assessment of Development Results - Somalia (Second Assessment) - United Nations Development Programme (United Nations, 2017)
This is the second Assessment of Development Results (ADR) conducted by the Independent Evaluation Office of UNDP in 2014 with a view to contributing to the realignment of the ongoing country programme (2011-2015) and the corresponding gender strategy to ensure consistency with: the Somali New Deal Compact, the UN Integrated Strategic Framework, the UNDP Strategic Plan (2014-2017) and the Gender Equality Strategy (2014-2017). In so doing the ADR will also contribute to the preparation of the new UNDP country programme that will begin in 2017.